Advertisement call of two threatened red-bellied-toads, Melanophryniscus cambaraensis and M. macrogranulosus (Anura: Bufonidae), from the Atlantic Rainforest, southern Brazil - Caorsi, Valentina; Bordignon, Debora Wolff; Márquez, Rafael; Borges-Martins, Márcio (Zootaxa, 2020)
In anuran amphibians, acoustic signals are fundamental mechanisms of mate recognition and mate choice, which makes frog calls a fundamental tool for anuran taxonomy. In this work, we describe the advertisement call of two species for the genus Melanophryniscus, M. cambaraensis and M. macrogranulosus and use the descriptions to try to solve a taxonomic problem between them. We collected data after heavy rains in three different sample sites in Rio Grande do Sul, Brazil, between 2012 and 2013. The advertisement call of both species is composed of two segments. It always begins with part A (about 0.44–6 seconds) composed of single modulated pulses separated by long time intervals. It is followed by part B, a long train of unmodulated pulses with short time intervals, lasting from 9 to 32.2 seconds. Principal Component Analysis (PCA) indicated some variation between temporal parameters of the two species, but Multivariate Analysis of Variance showed no significant differences. Within-individual Coefficient of Variation (CV) showed only two static parameters: pulse rate and peak frequency, both in the part B of the call. Despite intra-male variation in some acoustic parameters, it is not possible to differentiate between M. cambaraensis and M. macrogranulosus species only using bioacoustics.